Tetracycline-encapsulated P(3HB) microsphere-coated 45S5 Bioglass®-based scaffolds for bone tissue engineering - Meng, D.; Francis, L.; Thompson, I. D.; Mierke, Claudia; Hübner, Holger; Amtmann, A.; Roy, I.; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2013)
Bioglass®-based scaffolds for bone tissue engineering have been developed, which can also serve as carriers for drug delivery. For this, P(3HB) microspheres (PMSs) loaded with tetracycline were fabricated and immobilised on the scaffold surfaces by a modified slurry dipping technique. The sustained drug delivery ability in simulated body fluid was confirmed by using UV-Vis absorption spectroscopy measurements. The MTT assay using mouse fibroblast cells provided evidence that the tetracycline loaded microspheres produced in this study show limited cytotoxicity. The scaffolds developed in this work provide mechanical support, adequate 3D surface roughness, bioactivity and controlled drug delivery function, and are thus interesting candidates for bone tissue engineering applications. © 2013 Springer Science+Business Media New York.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.tetrac